1994
DOI: 10.2307/2410515
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Development in Drosophila melanogaster Selected for Postponed Senescence

Abstract: The role of development in the evolution of postponed senescence is poorly understood despite the existence of a major gerontological theory connecting developmental rate to aging. We investigate the role of developmental rate in the laboratory evolution of aging using 24 distinct populations of Drosophila melanogaster. We have found a significant difference between the larval developmental rates of our Drosophila stocks selected for early (B) and late-life (O) fertility. This larval developmental time differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 0 publications
1
62
3
Order By: Relevance
“…In D. melanogaster, the trade-off between adult size and fast development is well known (Partridge & Fowler, 1993 ;Zwaan et al, 1995 ;Nunney, 1996 ;Chippindale, 1997 ;Betran et al, 1998), suggesting that when rapid development is at a premium, the benefits of faster development may override those of larger size, leading to stabilizing selection on body size (Wilkinson, 1987). In populations maintained on a relatively short-generationtime, discrete-generation regime, such as the Bpopulations used in our study, development time is known to be under strong selection (Chippindale et al, 1994). Thus, we do not feel that our observation contradicts previous reports on the correlation of body size and male mating success under conditions of uncontrolled density in the field or the laboratory.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In D. melanogaster, the trade-off between adult size and fast development is well known (Partridge & Fowler, 1993 ;Zwaan et al, 1995 ;Nunney, 1996 ;Chippindale, 1997 ;Betran et al, 1998), suggesting that when rapid development is at a premium, the benefits of faster development may override those of larger size, leading to stabilizing selection on body size (Wilkinson, 1987). In populations maintained on a relatively short-generationtime, discrete-generation regime, such as the Bpopulations used in our study, development time is known to be under strong selection (Chippindale et al, 1994). Thus, we do not feel that our observation contradicts previous reports on the correlation of body size and male mating success under conditions of uncontrolled density in the field or the laboratory.…”
Section: Discussionmentioning
confidence: 85%
“…In most of these studies it is not clear whether larval density of populations and experimental flies was deliberately controlled at moderate levels or not, once again making a direct comparison with our results difficult. In Drosophila, larval density has a profound effect on many fitness components, and on correlations between them (Mueller, 1990 ;Joshi, 1997 ;Santos et al, 1997 ;Borash et al, 1998), and often differences in results can be due to inadvertent differences in culture densities (see Discussion in Chippindale et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, species inhabiting seasonal environments show high variance in their growth rates (Semlitsch, 1993;Bradshaw and Holzapfel, 1996) and one proposal is that variation might arise from adaptive plastic responses to variable environmental conditions (Abrams et al, 1996;Gotthard, 2001). Several studies have found costs and trade-offs associated with high growth rates in insects, with costs manifesting as higher juvenile mortality, decreased adult survival (Chippindale et al, 1994) or increased susceptibility to parasitism by bacteria and viruses (Sharpe and Detroy, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In this generation the accelerated treatments completed egg-to-adult development 15-17% faster than their controls. An earlier study of postponed aging populations (Chippindale et al 1994) showed no differences in hatching time between selection treatments differentiated for developmental time. Furthermore, Chippindale et al (1997) assumed that little or none of the evolutionary response was due to modification of egg duration.…”
Section: Discussionmentioning
confidence: 82%
“…The notion that Drosophila melanogaster in the wild has undergone continuous directional selection for developmental speed has led some authors to suspect lack of additive genetic variance for the failure of many artificial attempts to produce faster developing lines (Sang and Clayton 1957, Clarke et al 1961, Robertson 1963, Burnett et al 1977, Partridge and Fowler 1992. Some studies analyzing embryonic developmental time in populations selected for few generations showed no differences in hatching time between developmental time selection treatments (Chippindale et al 1994). Furthermore, selection for embryonic time produced very small differences, on the order of an hour or less between populations tested (Marinkovic andAyala 1986, Neyfakh andHartl 1994).…”
Section: Introductionmentioning
confidence: 99%